2008
DOI: 10.1016/j.pscychresns.2008.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Gray matter structural alterations in obsessive–compulsive disorder: Relationship to neuropsychological functions

Abstract: Numerous magnetic resonance (MR) studies have examined gray matter structural alterations in patients with obsessive-compulsive disorder (OCD). Few, however, have used automated, highly reliable techniques such as voxel-based morphometry (VBM) to examine the entire brain in contrast to selected regions of interest. Moreover, few studies have examined the functional correlates of gray matter abnormalities in OCD. We used VBM to evaluate regional gray matter differences between 21 OCD patients and 21 age-and sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 66 publications
(74 reference statements)
4
36
1
2
Order By: Relevance
“…These studies included 343 OCD patients (80 children and 263 adults) and 318 HC (69 children and 249 adults) (Pujol et al, 2004;Valente et al, 2005, Carmona et al, 2007Christian et al, 2008;Szeszko et al, 2008;Gilbert et al, 2008a, b;Yoo et al, 2008;Lázaro et al, 2009;Van den Heuvel et al, 2009). Study selection was performed by one author (J-YR) and independently verified by another (NL).…”
Section: Literature Search and Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies included 343 OCD patients (80 children and 263 adults) and 318 HC (69 children and 249 adults) (Pujol et al, 2004;Valente et al, 2005, Carmona et al, 2007Christian et al, 2008;Szeszko et al, 2008;Gilbert et al, 2008a, b;Yoo et al, 2008;Lázaro et al, 2009;Van den Heuvel et al, 2009). Study selection was performed by one author (J-YR) and independently verified by another (NL).…”
Section: Literature Search and Study Selectionmentioning
confidence: 99%
“…However, results from VBM studies have remained inconsistent and controversial. For example, some studies have found that OCD patients have greater OFC compared with control subjects (Valente et al, 2005;Szeszko et al, 2008;Yoo et al, 2008), and some other studies reported a smaller OFC in OCD patients (Pujol et al, 2004;Christian et al, 2008;Lázaro et al, 2009). Thus, a quantitative overview of VBM findings in OCD is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Several structural magnetic resonance imaging (MRI) studies, employing voxel-based morphometry (VBM), support this model [5], [6], [7], [8], [9]. For instance, Valente et al reported that patients with OCD showed increased grey matter in the left posterior orbitofrontal cortex, anterior insula, bilateral parahippocampal gyrus, and right fusiform gyrus, and decreased grey matter in the left anterior cingulate gyrus and medial frontal gyrus, compared with healthy controls [6].…”
Section: Introductionmentioning
confidence: 98%
“…The neurobiology of OCD has been hypothesized to lie within a framework involving the orbitofrontal-striatal circuit [2,3]. A number of voxel-based morphometry (VBM) studies conducted using statistical parametric mapping generally support this model, although findings have been inconsistent [47]. Valente and colleagues [7] found that OCD patients had more gray matter in the left posterior orbitofrontal cortex (OFC) and parahippocampal regions and less gray matter in the left anterior cingulate compared with matched controls.…”
Section: Introductionmentioning
confidence: 99%